Effects of nitrogen addition on microbial residues and their contribution to soil organic carbon in China's forests from tropical to boreal zone. (1st January 2021) - Ma, Suhui; Chen, Guoping; Du, Enzai; Tian, Di; Xing, Aijun; Shen, Haihua; Ji, Chengjun; Zheng, Chengyang; Zhu, Jianxiao; Zhu, Jiangling; Huang, Hanyue; He, Hongbo; et al.
Abstract: Atmospheric nitrogen (N) deposition has a significant influence on soil organic carbon (SOC) accumulation in forest ecosystems. Microbial residues, as by-products of microbial anabolism, account for a significant fraction of soil C pools. However, how N deposition affects the accumulation of soil microbial residues in different forest biomes remains unclear. Here, we investigated the effects of six/seven-year N additions on microbial residues (amino sugar biomarkers) in eight forests from tropical to boreal zone in eastern China. Our results showed a minor change in the soil microbial residue concentrations but a significant change in the contribution of microbial residue-C to SOC after N addition. The contribution of fungal residue-C to SOC decreased under low N addition (50 kg N ha −1 yr −1 ) in the tropical secondary forest (−19%), but increased under high N addition (100 kg N ha −1 yr −1 ) in the temperate Korean pine mixed forest (+21%). The contribution of bacterial residue-C to SOC increased under the high N addition in the subtropical Castanopsis carlesii forest (+26%) and under the low N addition in the temperate birch forest (+38%), respectively. The responses of microbial residue-C in SOC to N addition depended on the changes in soil total N concentration and fungi to bacteria ratio under N addition and climate. Taken together, these findings provide the experimental evidence that N addition diversely regulates the formation and composition of microbial-derived C in SOC in forest ecosystems. Graphical abstract: Image 1 Highlights: Soil microbial residues in forests showed minor changes under N addition. Microbial residue C in SOC increased under N addition in a subtropical forest. Bacterial residue C in SOC was increased by N addition in subtropical and temperate forests. Response of microbial derived C in SOC depended on soil N, fungi/bacteria and climate. Abstract : Nitrogen additions showed a minor effect on microbial residues, but significantly changed the contribution of microbial residue carbon to soil organic carbon in forests.